Young anatomist explorace program - Ker Woon, Choy; Adib Ridzuan, Nurul Raudzah (Faculty of Medicine, 2023)
The Department of Anatomy is excited to share our recent success of Young Anatomist ExploRACE, a program aiming to nurture and spark young children's curiosity in exploring and racing for Anatomy knowledge through a series of plays. To our knowledge, this is the first- ever program that exposes the knowledge of Anatomy in young children in the form of hands-on and games-based in Malaysia.